2010
DOI: 10.1371/journal.ppat.1000794
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization by Cryo-EM of the Mycobacterial Capsular Layer: A Labile Structure Containing ESX-1-Secreted Proteins

Abstract: The cell envelope of mycobacteria, a group of Gram positive bacteria, is composed of a plasma membrane and a Gram-negative-like outer membrane containing mycolic acids. In addition, the surface of the mycobacteria is coated with an ill-characterized layer of extractable, non-covalently linked glycans, lipids and proteins, collectively known as the capsule, whose occurrence is a matter of debate. By using plunge freezing cryo-electron microscopy technique, we were able to show that pathogenic mycobacteria produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
326
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 271 publications
(350 citation statements)
references
References 46 publications
21
326
0
3
Order By: Relevance
“…Colonies with reduced amounts of secreted PE_PGRS proteins were selected and re-checked for PE_PGRS secretion defects in a second double filter assay. In a similar assay, a selection of mutants was also tested with antiserum directed against the surface protein EspE (4,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonies with reduced amounts of secreted PE_PGRS proteins were selected and re-checked for PE_PGRS secretion defects in a second double filter assay. In a similar assay, a selection of mutants was also tested with antiserum directed against the surface protein EspE (4,25).…”
Section: Methodsmentioning
confidence: 99%
“…The natural antibiotic resistance of M. tuberculosis is partially due to its exceptionally hydrophobic and complex cell envelope structure. Although mycobacteria are classified as high GC Gram-positives, recent cryo-transmission electron microscopy unequivocally showed that the mycobacterial cell envelope consists of two membranes: a cytoplasmic membrane and a unique outer membrane (2)(3)(4). The inner leaflet of this atypical outer membrane consists of long chain fatty acids called mycolic acids, which are covalently linked to a periplasmic arabinogalactan polymer.…”
mentioning
confidence: 99%
“…If the target of protective antibodies was expressed on the mycobacterial surface, we reasoned that standard culture of mycobacteria in our experiments, which includes axenic growth in media containing the mild detergent Tween-80, might strip away some of the mycobacterial capsule components (28). We, therefore, grew Mtb either on 7H10 agar plated in the absence of Tween-80 or in axenic culture in supplemented 7H9 medium, which includes Tween-80, and then used the bacteria in the WBA.…”
Section: Significancementioning
confidence: 99%
“…In pathogenic mycobacteria, several different ESX systems exist and we were interested in identifying the secretion signal for these systems as well. Recently, we identified a putative ESX-1-dependent PPE substrate by proteomic analysis, i.e., M. marinum PPE68_1 (hereafter referred to as MmPPE68_1) (15). MmPPE68_1 is adjacent to PE35 (hereafter referred to as MmPE35) in a two-gene operon (Mmar_0185-Mmar_0186).…”
Section: Esx-5 Secretion Of M Tuberculosis Lipy Depends On a Similarmentioning
confidence: 99%
“…The archetypical T7S system, ESX-1, is responsible for the secretion of several proteins, including the ESX-1-encoded T-cell antigens ESAT-6 (early secreted antigenic target of 6 kDa) and CFP-10 (culture filtrate protein of 10 kDa) (7,(11)(12)(13)(14)(15). ESX-1 and its substrates play an important, albeit not yet fully understood role in M. tuberculosis virulence.…”
mentioning
confidence: 99%